An Introduction to Food Science Technology & Quality Management - Devendra Kumar Bhatt; Priyanka Tomar (Ludhiana Kalyani, 2006)
This book is an interdisiplinary subject involving primary bacteriology, chemistry, biology and Engineering.
Plant Food Animal Foods Fermented Foods
Keywords: Plant Food ,Animal Foods, Fermented Foods